2011
DOI: 10.1007/s00330-011-2077-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thoracic aortic elasticity: a preliminary study using electrocardiographically gated dual-source CT

Abstract: The properties of aortic pulsation and wall elasticity could be well shown by ECG-gated DSCT. The new findings regarding segment difference and age relevance were significant and should be taken into account in clinical trials and treatments for the elasticity related cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…Our data did not reveal any significant correlation between aortic wall motion and age. These findings differ from those present in the literature [11,19,22] and might be due to the small sample size. Ganten et al [11] showed an age-dependent decrease of aortic wall elasticity using ECG-CTA.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our data did not reveal any significant correlation between aortic wall motion and age. These findings differ from those present in the literature [11,19,22] and might be due to the small sample size. Ganten et al [11] showed an age-dependent decrease of aortic wall elasticity using ECG-CTA.…”
Section: Discussioncontrasting
confidence: 99%
“…Metafratzi et al [19], in a MR-study, showed that aortic distensibility decreased with age and was correlated with various diseases, such as hypertension and atherosclerosis. More recently, Li et al [22] evaluated 56 healthy patients using dynamic CTA showing an agedependent decrease of elasticity of the thoracic aorta, considered as due to the natural aging of such vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, preoperative assessment in obese patients is very difficult, and its accuracy can be significantly altered by visceral fat and bowel gasses, especially by the operators; therefore detecting aneurysm change with ultrasound is often unpredictable and highly variable. Recent studies have indicated that CT could be well used to assess area and distensible changes in animal or human aorta [913]. A strength of CT is the unique ability to provide both local and regional noninvasive measurement of aortic morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that aortic distensibility, or elasticity, decreases with age and with the presence of atherosclerotic disease. [11][12][13][14][15] In addition, it is generally thought that the aorta becomes longer and more tortuous with age. [16][17][18][19] The mean age of our trauma population was 14 years and 29 years younger than our dissection and aneurysm patients, respectively, and it is reasonable to assume that the trauma patients in our sample have more compliant aortas compared with the older patients with dissection or aneurysmal disease.…”
Section: Resultsmentioning
confidence: 99%